Kwestie kulturowe w referendach szwajcarskich w latach 2000-2020 (Politeja, 2023)
CULTURAL ISSUES IN SWISS REFERENDA BETWEEN 2000 AND 2021Switzerland is one of few countries where popular referenda are an integral part of political life. These can be held on a variety of issues. Out of 186 proposals voted in the country between 2000 and 2021, this article analyses 17 related to culture in its broadest sense. The chosen examples include both specific issues as well as those fundamental to society, such as the right to abortion or the legal status of same-sex marriage. Typically, votes on cultural issues do not draw much public interest. The turnout rarely exceeds 50%, leaving decisions which affect the whole society to a minority of those eligible to vote. It should be stressed that, in some cases, referenda on cultural issues are a clear example of positivist belief that law is man-made.